EFL High School Teachers’ Continuing Professional Development: The Costa Rican Experience - García Castro, Verónica (2023)
Home Continuing Professional Development of TESOL Practitioners Chapter EFL High School Teachers’ Continuing Professional Development: The Costa Rican Experience Verónica García-Castro & Max Arias Segura Chapter First Online: 28 November 2023 14 Accesses 1 Altmetric Part of the Springer Texts in Education book series (SPTE) Abstract Continuing professional development (CPD) is crucial to enhance in-service teachers’ pedagogical skills and their overall careers. However, CPD practices for EFL teachers vary depending on the teaching context, and some practices are still undeveloped. The aim of this chapter is to provide a glimpse of what CPD for EFL teachers looks like in Costa Rica by drawing attention to CPD practices implemented in secondary education. A description of some CPD providers with examples of successful CPD training and lessons learnt is discussed. The chapter also reflects upon how to improve CPD for EFL teachers in Costa Rica and puts forward ideas to build national coordination among CPD providers. It concludes with priorities for future CPD practices to enhance the CPD training EFL teachers receive in Costa Rica.